2020
DOI: 10.18632/aging.202281
|View full text |Cite
|
Sign up to set email alerts
|

Integrated bioinformatic analysis of RNA binding proteins in hepatocellular carcinoma

Abstract: RNA binding proteins (RBPs) are aberrantly expressed in a tissue-specific manner across many tumors. These proteins, which play a vital role in post-transcriptional gene regulation, are involved in RNA splicing, maturation, transport, stability, degradation, and translation. We set out to establish an accurate risk score model based on RBPs to estimate prognosis in hepatocellular carcinoma (HCC). RNA-sequencing data, proteomic data and corresponding clinical information were acquired from the Cancer Genome Atl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 69 publications
(43 reference statements)
1
15
0
Order By: Relevance
“…It was reported that in lung adenocarcinoma, colorectal cancer, and breast cancer, GTPBP4 showed a trend of upregulated expression [ 19 , 24 , 25 ]. In addition, we also found that liver cancer patients with upregulated expression of GTPBP4 showed a shorter overall survival time ( P =0.02), which is consistent with the results of previous studies [ 26 , 27 ]. The expression of GTPBP4 was positively correlated with the invasion of B cells and macrophages, which may be one of the reasons why the expression of GTPBP4 can affect the overall survival time of liver cancer patients.…”
Section: Discussionsupporting
confidence: 92%
“…It was reported that in lung adenocarcinoma, colorectal cancer, and breast cancer, GTPBP4 showed a trend of upregulated expression [ 19 , 24 , 25 ]. In addition, we also found that liver cancer patients with upregulated expression of GTPBP4 showed a shorter overall survival time ( P =0.02), which is consistent with the results of previous studies [ 26 , 27 ]. The expression of GTPBP4 was positively correlated with the invasion of B cells and macrophages, which may be one of the reasons why the expression of GTPBP4 can affect the overall survival time of liver cancer patients.…”
Section: Discussionsupporting
confidence: 92%
“…Aberrant expression of RBPs has been shown across many malignant tumors, including HCC [98,99]. A high score based on the expression of these RBPs was associated with poor overall survival of HCC [99].…”
Section: Rna-binding Proteinsmentioning
confidence: 93%
“…Aberrant expression of RBPs has been shown across many malignant tumors, including HCC [98,99]. A high score based on the expression of these RBPs was associated with poor overall survival of HCC [99]. Another study showed that aberrant expression of four key RBPs, including mitochondrial ribosomal protein L54 (MRPL54), enhancer of zeste homolog 2 (EZH2), PPARγ coactivator 1 alpha (PPARGC1A), and eukaryotic translation initiation factor 2-alpha kinase 4 (EIF2AK4), can be applied to HCC prognosis [100].…”
Section: Rna-binding Proteinsmentioning
confidence: 99%
“…One study integrated multi-omics analysis, such as RNA-seq, Ribosome profiling and quantitative mass spectrometry, uncovered that an RNA element derived from HBV enhancer I forms a stem-loop which suppresses HBV translation ( 150 ). Furthermore, 11 RBPs (RAN, BRIX1, SMG5, DYNC1H1, PRKDC, GTPBP4, and so on) are associated with the overall survival of HCC patients by integrating RNA sequencing and proteomic data ( 13 ). These RBPs bind to various RNAs, such as mRNAs, rRNAs, ncRNAs, play a critical role in post-transcriptional gene regulation (PTGR) and are associated with RNA splicing, transport, maturation, degradation, stability, and translation ( 151 ).…”
Section: Proteomics Characteristicsmentioning
confidence: 99%
“…"Omics" technologies are used to mainly detect all protein, transcripts, and metabolites for mining for available data in the biological sample. These high-throughput technologies play critical roles in describing gene and/or protein expression profiles, and their effects on HBV-associated HCC (12)(13)(14). Although many biomarkers for diagnosis and prognosis have been identified through omics analysis of HBV infection, the previous studies focus on a single aspect of the natural history of CHB.…”
Section: Introductionmentioning
confidence: 99%